2050 LCOE (Levelized Cost of Energy) projection for a hybrid PV (photovoltaic)-CSP (concentrated solar power) plant in the Atacama Desert, Chile. (1st January 2016) - Parrado, C.; Girard, A.; Simon, F.; Fuentealba, E.
Abstract: This study calculates the LCOE (Levelized Cost of Energy) on the PSDA (Atacama Solar Platform) for a solar–solar energy mix with the objective of evaluate new options for continuous energy delivery. LCOE was calculated for three 50 MW (megawatt) power plants: A PV (photovoltaic), a CSP (concentrated solar power) plant with 15 h TES (thermal energy storage) and a hybrid PV-CSP plant constituted with 20 MWp of PV and 30 MW of CSP with 15 h TES. Calculations present two scenario projections (Blue Map and Roadmap) until 2050 for each type of plant. Due to the huge solar resource available in northern Chile, the PV-CSP hybrid plant results to be a feasible option for electricity generation, as well as being effectively able to meet electricity demand profile of the mining industry present in the area. This type of energy could mitigate long-term energy costs for the heavy mining activity, as well as the country CO2 emissions. Findings point out that PV-CSP plants are a feasible option able to contribute to the continuous delivery of sustainable electricity in northern Chile. Moreover, this option can also contribute towards electricity price stabilization, thus benefiting the mining industry, as well as reducing Chile's carbon footprint. Highlights: The Atacama Desert has the world highest amount of solar resource. PV-CSP hybrid plant offers a sustainable solution for electricity generation. PV-CSP hybrid plant model appears to be a feasible model for electricity generation and delivery. This hybrid plant model should be considered by investors as a lucrative international option for energy generation. This type of energy could mitigate long-term energy costs for the heavy mining activity in this area.